2003
DOI: 10.1577/1548-8454(2003)065<0049:pioevi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Potential Indicators of Egg Viability in Landlocked Fall Chinook Salmon Spawn with or without the Presence of Overripe Eggs

Abstract: Selected reproductive characteristics obtained during the spawning of landlocked fall chinook salmon Oncorhynchus tshawytscha from Lake Oahe, South Dakota, were evaluated for their use as predictors of embryo survival to the eyed egg stage. Spawn was categorized according to the presence or absence of observable overripe eggs. No significant differences in female length, female weight, the number of eggs per female, egg size, the amount of ovarian fluid released during spawning, and ovarian fluid specific grav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
1
16
1
Order By: Relevance
“…Our pH results for chinook salmon roe are lower than the 7.94 ± 0.04 reported for chinook salmon (Barnes, Sayler, & Cordes, 2003). This might be related to the sample preparation.…”
Section: Phcontrasting
confidence: 92%
See 2 more Smart Citations
“…Our pH results for chinook salmon roe are lower than the 7.94 ± 0.04 reported for chinook salmon (Barnes, Sayler, & Cordes, 2003). This might be related to the sample preparation.…”
Section: Phcontrasting
confidence: 92%
“…This might be related to the sample preparation. Direct pH measurements on homogenised roes, as in the present study (Table 1) and other reports (Gagné & Adambounou, 1994;Katsiadaki, Taylor, & Smith, 1999) resulted in a lower pH range compared with other studies (Barnes et al, 2003;Fauvel et al, 1993;Lahnsteiner, Weismann, & Patzner, 1999) which measured the pH of the ovarian fluids after separation of solids by filtration. Thus Katsiadaki et al (1999) reported a pH range between 5.68 and 6.96 for cod (Gadus morhua) roe while Fauvel et al (1993) found the pH of ovarian fluids from turbot (Scophthalmus maximus) ranged from 7.0 to 8.2, and Lahnsteiner et al (1999) reported that trout (Salmo trutta lacustris) roe pH ranged between 8 and 9.…”
Section: Phsupporting
confidence: 65%
See 1 more Smart Citation
“…Oncorhynchus tshawytscha from Lake Oahe, South Dakota, typically exhibit poor survival during hatchery incubation, and survival varies dramatically from female to female (Barnes et al 2000a(Barnes et al , 2003. Because of the highly variable egg survival and the relatively high cost associated with incubating potentially nonviable eggs during hatchery rearing, the ability to eliminate poor-quality spawns immediately after removal from the female would lead to improvements in spawning efficiencies and cost reductions.…”
Section: Eggs Of Landlocked Fall Chinook Salmonmentioning
confidence: 99%
“…Additionally, objective quantitative egg assessments have also been used with mixed results (Satia et al 1974;Fauvel et al 1993;Lahnsteiner et al 1999Lahnsteiner et al , 2001Barnes et al 2000bBarnes et al , 2003.…”
Section: Eggs Of Landlocked Fall Chinook Salmonmentioning
confidence: 99%